Students Perceptions of Service Quality and Promotion of Interest in Using Wadiah Contract in Islamic Banks - Ellisa Nur Amelia; Mira Rahmi; Lili Puspita Sari (Journal of Islamic Economics and Social Science (JIESS), 2021)
Users of wadiah savings accounts are more desirable in Islamic banks, this can be seen from the amount of wadiah savings in the financing data and third party funds of Islamic commercial banks in Islamic Banking Statistics 2020. The increase in users of wadiah savings accounts occupies 1.2% compared to mudharabah savings. The purpose of this study was to determine student perceptions of service quality and promotion of interest in using wadiah contracts in Islamic banks. This analysis uses service quality and promotion as independent variables. The dependent variable is interest. The sample of this research is students who have savings at Bank Syariah Mandri, Bank Negara Indonesia Syariah and Bank Rakyat Indonesia Syariah. Collecting data using a questionnaire that was distributed directly as many as 100 questionnaires. The method used in this research is multiple linear regression analysis, with hypothesis testing t test and f test. The results of this study indicate that service quality has a significant positive effect on interest, while promotion has a positive but not significant effect on interest. For service quality and promotion together have a significant positive effect on interest. The results of this study in the future contribute to the increase in Islamic bank customers through the use of wadiah contracts by improving the quality of services they have and increasing the promotions created.